Strategi Pengelolaan dan Pengembangan Pesantren Salaf - Rojudin (JMPT: Jurnal Manajemen Pendidikan Tihamah, 2023)
Pesantren, Indonesia's oldest educational institution, has played a significant role in Islamic education. This article explores the management and development strategies for salaf pesantren. It delves into historical context, discussing the unique elements of pesantren: kyai (teachers), santri (students), pondok (boarding), masjid (mosque), and classical book teachings. Challenges include centralized leadership, management complexities, and the need for professional human resources. The article proposes solutions, encompassing financial management, personalized student guidance, result evaluation principles, structural management, socio-egalitarianism, epistemology or methodology mastery, continuous innovation, and economic empowerment. The paper also emphasizes innovation, aligned curriculum, and cooperation among pesantren and related institutions. It concludes that pesantren can thrive by embracing modern strategies while preserving core values.